Lawrence Dewan and Form as Something Divine in Things - Serra Pérez, Manuel Alejandro (Anales del Seminario de Historia de la Filosofía, 2024)
The main disputes that have taken place within contemporary Thomism have been marked by a strong criticism of the Dominican Thomistic school. The most disputed theses can be summarised around the understanding of esse and its emphasis on the whole philosophy of being. The Canadian Dominican Lawrence Dewan wanted to counter this criticism by balancing this emphasis on esse by asserting the role of form in Thomas Aquinas’ thought. Form, which is something divine in things, is not merely a receptive power, but the cause of esse and the mediator of the creative act of the entity. In this article we will study in detail the main ideas of Dewanian Thomism in the light of the most original aspects of Aquinas’ teaching, from a critical perspective.